Chest physiotherapy improves lung aeration in hypersecretive critically ill patients: a pilot randomized physiological study - Federico Longhini; Andrea Bruni; Eugenio Garofalo; Chiara Ronco; Andrea Gusmano; Gianmaria Cammarota; Laura Pasin; Pamela Frigerio; Davide Chiumello; Paolo Navalesi (Critical Care, 2020)
Abstract Background Besides airway suctioning, patients undergoing invasive mechanical ventilation (iMV) benefit of different combinations of chest physiotherapy techniques, to improve mucus removal. To date, little is known about the clearance effects of oscillating devices on patients with acute respiratory failure undergoing iMV. This study aimed to assess (1) the effects of high-frequency chest wall oscillation (HFCWO) on lung aeration and ventilation distribution, as assessed by electrical impedance tomography (EIT), and (2) the effect of the association of HFCWO with recruitment manoeuvres (RM). Methods Sixty critically ill patients, 30 classified as normosecretive and 30 as hypersecretive, who received ≥ 48 h of iMV, underwent HFCWO; patients from both subgroups were randomized to receive RM or not, according to two separated randomization sequences. We therefore obtained four arms of 15 patients each. After baseline record (T0), HFCWO was applied for 10 min. At the end of the treatment (T1) or after 1 (T2) and 3 h (T3), EIT data were recorded. At the beginning of each step, closed tracheobronchial suctioning was performed. In the RM subgroup, tracheobronchial suctioning was followed by application of 30 cmH2O to the patient’s airway for 30 s. At each step, we assessed the change in end-expiratory lung impedance (ΔEELI) and in tidal impedance variation (ΔTIV), and the center of gravity (COG) through EIT. We also analysed arterial blood gases (ABGs). Results ΔTIV and COG did not differ between normosecretive and hypersecretive patients. Compared to T0, ΔEELI significantly increased in hypersecretive patients at T2 and T3, irrespective of the RM; on the contrary, no differences were observed in normosecretive patients. No differences of ABGs were recorded. Conclusions In hypersecretive patients, HFCWO significantly improved aeration of the dorsal lung region, without affecting ABGs. The application of RM did not provide any further improvements. Trial registration Prospectively registered at the Australian New Zealand Clinical Trial Registry ( www.anzctr.org.au ; number of registration: ACTRN12615001257550; date of registration: 17th November 2015).